Ancient Martian aeolian processes and palaeomorphology reconstructed from the Stimson formation on the lower slope of Aeolis Mons, Gale crater, Mars. Issue 4 (12th April 2018) - Banham, Steven G.; Gupta, Sanjeev; Rubin, David M.; Watkins, Jessica A.; Sumner, Dawn Y.; Edgett, Kenneth S.; Grotzinger, John P.; Lewis, Kevin W.; Edgar, Lauren A.; Stack‐Morgan, Kathryn M.; Barnes, Robert; Bell, James F.; et al.
Abstract: Reconstruction of the palaeoenvironmental context of Martian sedimentary rocks is central to studies of ancient Martian habitability and regional palaeoclimate history. This paper reports the analysis of a distinct aeolian deposit preserved in Gale crater, Mars, and evaluates its palaeomorphology, the processes responsible for its deposition, and its implications for Gale crater geological history and regional palaeoclimate. Whilst exploring the sedimentary succession cropping out on the northern flank of Aeolis Mons, Gale crater, the Mars Science Laboratory rover Curiosity encountered a decametre‐thick sandstone succession, named the Stimson formation, unconformably overlying lacustrine deposits of the Murray formation. The sandstone contains sand grains characterized by high roundness and sphericity, and cross‐bedding on the order of 1 m in thickness, separated by sub‐horizontal bounding surfaces traceable for tens of metres across outcrops. The cross‐beds are composed of uniform thickness cross‐laminations interpreted as wind‐ripple strata. Cross‐sets are separated by sub‐horizontal bounding surfaces traceable for tens of metres across outcrops that are interpreted as dune migration surfaces. Grain characteristics and presence of wind‐ripple strata indicate deposition of the Stimson formation by aeolian processes. The absence of features characteristic of damp or wet aeolian sediment accumulation indicate deposition in a dry aeolian system. Reconstruction of the palaeogeomorphology suggests that the Stimson dune field was composed largely of simple sinuous crescentic dunes with a height of ca 10 m, and wavelengths of ca 150 m, with local development of complex dunes. Analysis of cross‐strata dip azimuths indicates that the general dune migration direction and hence net sediment transport was towards the north‐east. The juxtaposition of a dry aeolian system unconformably above the lacustrine Murray formation represents starkly contrasting palaeoenvironmental and palaeoclimatic conditions. Stratigraphic relationships indicate that this transition records a significant break in time, with the Stimson formation being deposited after the Murray formation and stratigraphically higher Mount Sharp group rocks had been buried, lithified and subsequently eroded.